Controlling factors of symbiotic disaster between coal gas and spontaneous combustion in longwall mining gobs. (15th October 2016) - Xia, Tongqiang; Zhou, Fubao; Wang, Xinxin; Zhang, Yifan; Li, Yimin; Kang, Jianhong; Liu, Jishan
Graphical abstract: Coal-gas-heating interactions in longwall mining gob areas. Highlights: A symbiotic model between coal gas flow and combustion was extended through our previous model. The new model was applied to investigate the effects of controlling factors on symbiotic disaster. Contradictory relations are numerically investigated in the control of gob symbiotic disaster. Simulations can provide guidelines to design and optimize longwall mining parameters. Abstract: Underground methane-rich and combustion-prone longwall mining gobs are usually subjected to the symbiotic thread between coal gas and combustion disasters. Quantitative understanding of this symbiosis is essential to mitigate these potential disasters. However, previous mathematical models mainly focused on the simulation disaster of coal gas flow in gobs or spontaneous combustion, less attention is paid to the symbiosis between them. In this study, we extended a fully coupled coal-oxygen-heating model for the spontaneous combustion into a symbiotic model between coal gas flow and spontaneous combustion. This was achieved through the introduction of an accumulative gas release function in the set of coupled governing equations. The function defines the mass exchange of coal gas between gob and surrounding areas. We applied the symbiotic model to investigate the sensitivity of the symbiotic disaster to the controlling factors, including (1) ventilation flux; (2) face advance rate; (3) longwall panel width; and (4) coal-oxidation rate. Our results show that enhancing ventilation flux can dilute the CH4 concentration of return airway or working face, but increase the risk of gob spontaneous combustion. On the contrary, accelerating face advance rate can suppress gob spontaneous combustion, but easily cause CH4 concentration overrun of return airway or working face. That is, if parameters such as ventilation flux and face advance rate were not designed properly, a disaster (i.e. gas disaster) might be suppressed, but another disaster (i.e. spontaneous combustion) could be triggered or aggravated. In addition, widening longwall panel could aggravate gob leakage flux and improve the CH4 concentration of return airway, while it might exert less influence on coal self-heating. These results may provide some guidelines on how to mitigate the symbiotic disaster between coal gas flow and spontaneous combustion in longwall gobs.